Analisis Risk Asset Portfolio Berbasis Reward To Variability Pada Saham Syariah Di Indonesia Menggunakan Nonlinear Programming - Noor Saif Muhammad Mussafi (Mathematics Department, Faculty of Science and Technology, UIN Sunan Ampel Surabaya, 2017)
This research seeks to analyze the development of syariah stock optimization method using Nonlinear Programming in order to provide an optimal portfolio as a reference in improving the quality of syariah capital market in Indonesia. The research design used is descriptive qualitative by presenting a Shariah stock history data within a certain period that is analyzed and modeled for later sought solving. The data in this research is the stock price information syariah incorporated in the Jakarta Islamic Index (JII). Selected data with Reward to Variability (RVAL) were then analyzed using theories in financial mathematics and developed using quadratic programming. The result of this research is systematic step formulation to maximize profit level and minimize risk level of syariah share investment incorporated in JII in January 2015-December 2016 time domain. This research also concludes that by this method can be known the proportion of funds that can be invested in five best issuers. In the sample taken, for the expected profit level of 5.5% to 7.5%, then an investor is advised to embed its shares consecutively to AKRA, ICBP, PTPP, TLKM and WSKT on average of 29.74% ; 13.42%; 18.14%; 29.58%; And 9.1% with risk between 0.028301593% to 0.029386615%.